2020
DOI: 10.3390/biom10081179
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation with Sugar Beet Fructooligosaccharides and Garlic Residues Promotes Growth of Beneficial Bacteria and Increases Weight Gain in Neonatal Lambs

Abstract: The proper development of the early gastrointestinal tract (GIT) microbiota is critical for newborn ruminants. This microbiota is susceptible to modification by diverse external factors (such as diet) that can lead to long-lasting results when occurring in young ruminants. Dietary supplementation with prebiotics, ingredients nondigestible and nonabsorbable by the host that stimulate the growth of beneficial GIT bacteria, has been applied worldwide as a potential approach in order to improve ruminant health and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 83 publications
(109 reference statements)
0
4
0
Order By: Relevance
“…2,14 Several studies have explored the physiological functions of Veillonella in maintaining the dynamic balance between lactic acid and SCFAs and its relevance to host health and disease. 15,16 A few studies have observed lactic acid accumulation in the medium when Veillonella strains are co-cultured with Enterococcus faecium 17 or found that the medium cultured with Lactobacillus and Veillonella isolated from chicken cecum inhibits pathogenic intestinal bacteria. 18…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,14 Several studies have explored the physiological functions of Veillonella in maintaining the dynamic balance between lactic acid and SCFAs and its relevance to host health and disease. 15,16 A few studies have observed lactic acid accumulation in the medium when Veillonella strains are co-cultured with Enterococcus faecium 17 or found that the medium cultured with Lactobacillus and Veillonella isolated from chicken cecum inhibits pathogenic intestinal bacteria. 18…”
Section: Introductionmentioning
confidence: 99%
“…2,14 Several studies have explored the physiological functions of Veillonella in maintaining the dynamic balance between lactic acid and SCFAs and its relevance to host health and disease. 15,16 A few studies have observed lactic acid accumulation in the medium when Veillonella strains are cocultured with Enterococcus faecium 17 or found that the medium cultured with Lactobacillus and Veillonella isolated from chicken cecum inhibits pathogenic intestinal bacteria. 18 One of the crucial functions of Veillonella is the fermentation of organic acids to produce SCFAs; while some Veillonella strains cannot ferment carbohydrates such as glucose and lactose, they can ferment organic acids such as pyruvate and lactic acid into acetic acid and propionic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the decrease in Enterobacter and the increase in Bifidobacterium and Lactobacillus were observed in the anthocyanin group. In fact, both Bifidobacterium and Lactobacillus are well-known beneficial microbiota [52], also representing spread probiotic matrices sold on the market [53]. Bifidobacterium has been reported to stimulate the early development of gut regulating its microbial homeostasis, inhibiting pathogens and modulating local and systemic immune responses, improving vitamins production and increasing the bioconversion of dietary components to active compounds [54].…”
Section: Discussionmentioning
confidence: 99%
“…Animal microbiome research often focuses on the microbial populations that inhabit the gastrointestinal tract (GIT) of animals, in order to determine their role in the animal’s growth, health and disease ( Maynard et al, 2012 ; Van Borm et al, 2015 ; Bahrndorff et al, 2016 ; Celi et al, 2017 ; Peixoto et al, 2021 ). Functional insights into the animal’s GIT microbiome will lead to advances in animal disease prevention and nutrition through the targeted administration of probiotics, prebiotics, feed additives and customized diets ( de Lange et al, 2010 ; Kiarie et al, 2013 ; Dawood et al, 2018 ; Quijada et al, 2020a ). Effective functionality of the GIT and its health are important factors in determining animal performance (e.g., body weight gain and milk, meat, and egg production and quality; Celi et al, 2017 ).…”
Section: Example Success Storiesmentioning
confidence: 99%